DIVERSITY AND ABUNDANCE OF ECHINODERMS AT WEDA BAY WATERS, NORTH MALUKU - Abdul Wahab Radjab; Semuel Agustinus Rumahenga; Ahmad Soamole; Dominggus Polnaya; Wempy Barends (Department of Marine Science and Technology, Faculty of Fisheries and Marine Science, IPB University, 2014)
Weda Bay located at Halmahera Island, North Maluku was rich in fishes, sea cucumbers, crabs, shrimp, and alge resources. Research on diversity and density of echinoderms at Weda Bay, North Maluku was limited and therefore it was lack on data and information of the biota. The purpose of this study was to determine the diversity and density of echinoderms at Weda Bay, North Maluku. This research was conducted in March 2013 including transects and free collection of 6 stations contained echinoderms. The results showed that the overall echinoderms were found 23 species of 17 generas, 12 families, 10 orders, and 5 classes. Based on classes, the highest density of echinoderms was Asteroidea of 0.0456 ind/m2 (43.76 %) foundin the seagrass sand habitat. Meanwhile, the lowest density was Crinoidea of 0.0002 ind/m2 (0.19%) found in corals habitats. Keywords: diversity, density, echinoderms, Weda bay, North Maluku.